Developing A Three-Dimensional Model of Khanaqin High lands by using Blender Program, Mount Bamu as an Example - Mohammed, Ammar Hussein (Journal of Humanities & Social Sciences, 2024)
Modern technologies are considered one of the means to support studies of earth sciences, including geography, which have benefited greatly from the quantitative and technical revolution, This research came to present a model of modern technologies that can be harnessed to serve geomorphological studies, The research used descriptive and analytical methods. The research aims to use Blender software and harness its high potential The program is free and open source, and has a high ability to edit and modify, to develop a 3D model of Bamu mount area, by taking advantage of digital elevation models (DEM) extracted from NASA's SRTM radar images, as well as from Google aerial images , A 3D model section of the study area was built combining graphic design and geospatial data, The work involved collecting and defining geospatial data about the area, then processing this data, and then converting the derived map into a 3D model. The results of the work showed the high performance of the program in editing high-definition video, As well as displaying three-dimensional images with high coloring ability that helped in the interpretation and analysis of various phenomena by simulating the study area The current study recommends the necessity of applying this work to different regions in case there is a need to simulate the natural reality of those regions to assist in interpretation, analysis, and making appropriate decisions.
Keywords: Model; Blender; Bamu; mountain; Khanqen; 3D